Effect of women’s empowerment on lowering the number of children ever born in Bangladesh - Shanjida Chowdhury; Md. Aminul Haque (BMC Women's Health)
Abstract Introduction Women’s empowerment (WE) has become a central focus for development at a national and global level. There is a need for a comprehensive and updated assessment of the existing evidence on WE and the total number of children ever born (CEB). This paper addresses the association between different dimensions of WE and the total number of CEB among women aged 15–49 years in Dhaka, Bangladesh. Methods This is a cross-sectional study. Using primary data, two binary and skewed regression models were applied to find the best-fitting model to investigate the association between different dimensions of women’s empowerment and the total number of CEB. Results Based on the Akaike Information Criterion (AIC) and the Bayesian Information Criterion (BIC) principles, the best-fit model was the binary logistic regression compared to other models. The study revealed that higher levels of women empowerment were associated with fewer CEB. Among the four dimensions—economic, psychological, household, and socio-cultural indices- psychological dimensions significantly influenced the number of CEB. Results also showed that age at first marriage, educational attainment of respondents, occupational level, wealth index, and use of contraceptives were found to be negatively associated with the number of CEB. Conclusion The study found that an increase in WE was linked to a reduction in CEB. Other predictors for CEB were age at first marriage, women’s educational attainment, working status, wealth index, and contraceptive use, which were all identified as factors associated with a lower number of children. Policymakers should focus on the dimension-specific and overall level of WE in reducing CEB.